76.27.3 problem 3

Internal problem ID [17849]
Book : Differential equations. An introduction to modern methods and applications. James Brannan, William E. Boyce. Third edition. Wiley 2015
Section : Chapter 6. Systems of First Order Linear Equations. Section 6.5 (Fundamental Matrices and the Exponential of a Matrix). Problems at page 430
Problem number : 3
Date solved : Tuesday, January 28, 2025 at 11:04:01 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=3 x_{1} \left (t \right )-4 x_{2} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=x_{1} \left (t \right )-x_{2} \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.062 (sec). Leaf size: 30

dsolve([diff(x__1(t),t)=3*x__1(t)-4*x__2(t),diff(x__2(t),t)=1*x__1(t)-1*x__2(t)],singsol=all)
 
\begin{align*} x_{1} \left (t \right ) &= {\mathrm e}^{t} \left (c_{2} t +c_{1} \right ) \\ x_{2} \left (t \right ) &= \frac {{\mathrm e}^{t} \left (2 c_{2} t +2 c_{1} -c_{2} \right )}{4} \\ \end{align*}

Solution by Mathematica

Time used: 0.002 (sec). Leaf size: 41

DSolve[{D[x1[t],t]==3*x1[t]-4*x2[t],D[x2[t],t]==1*x1[t]-1*x2[t]},{x1[t],x2[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} \text {x1}(t)\to e^t (2 c_1 t-4 c_2 t+c_1) \\ \text {x2}(t)\to e^t ((c_1-2 c_2) t+c_2) \\ \end{align*}